732 Chemerin reactivates PTEN and suppresses PD-L1 in tumor cells via a novel CMKRL1-mediated pathway. (9th November 2020) - Pachynski, Russell; Rennier, Keith; Shin, Woo Jae; Krug, Ethan; Virdi, Gurpal; Pachynski, Russell
Abstract : Background: Chemokines and chemoattractants play critical roles in trafficking that help regulate leukocyte infiltrates in the tumor microenvironment. Chemokines/chemoattractants can also modulate tumor cell phenotype and function, as tumor cells express functional receptors for these agents. Chemerin (retinoic acid receptor responder 2, RARRES2) is an endogenous leukocyte chemoattractant that recruits innate immune cells through its receptor, CMKLR1. RARRES2 is widely expressed in nonhematopoietic tissues and often downregulated across multiple tumor types compared with normal tissue. We and others have shown that augmenting chemerin in the tumor microenvironment significantly suppresses tumor growth, in part, by immune effector cell recruitment. As chemerin has various roles outside of leukocyte trafficking (eg adipocyte differentiation and metabolic processes), we hypothesized that it may have additional, tumor-intrinsic effects. Methods: We investigated the effect of exogenous chemerin on human prostate and sarcoma tumor lines. Key signaling pathway components were elucidated using qPCR, Western blotting, siRNA knockdown, and specific inhibitors. Functional consequences of chemerin treatment were evaluated using in vitro and in vivo studies. Results: We show for the first time that human tumors exposed to exogenous chemerin significantly upregulate PTEN expression/activity, and concomitantly suppress programmed death ligand-1 (PD-L1) expression. CMKLR1 knockdown abrogated chemerin- induced PTEN and PD-L1 modulation, revealing a novel CMKLR1/PTEN/PD-L1 signaling cascade. Targeted inhibitors suggest that signaling occurs through the PI3K/AKT/mTOR pathway. We found that chemerin treatment significantly reduced tumor migration, while significantly increasing T-cell–mediated cytotoxicity. Chemerin treatment was as effective as both PD-L1 knockdown and the anti–PD-L1 antibody atezolizumab in augmenting T cell mediated tumor lysis. Forced expression of chemerin in human DU145 prostate tumors significantly suppressed in vivo tumor growth, significantly increasing PTEN and decreasing PD-L1 expression. Primary prostate tumor cultures that were treated with recombinant chemerin showed significant increases in PTEN and decreases in PD-L1 expression compared to controls. Lastly, analyses of clinical trial data from human metastatic prostate cancer patients receiving treatment with ipilimumab (NCT02113657 ) showed higher tumoral levels of RARRES2 expression correlated with higher levels of PTEN, higher effector immune cell (eg cytotoxic T cells, NK cells) signatures, and improved clinical outcomes, suggesting a strategy to augment chemerin/RARRES2 levels in tumors may improve responses to immunotherapy. Conclusions: Collectively, our data show for the first time a novel link between chemerin, PTEN, and PD-L1 in human tumor lines. These results show that chemerin – in addition to its ability to suppress tumor growth by recruitment of immune effector cells, may also have a role in improving T-cell–mediated immunotherapies through favorable modulation of PTEN and PD-L1.